Technical and Economic Advantages of Turbo-Drive Variant with TRB Turbines over Turbo-Generator Variant in Low Power Engineering - N. V. Panteley (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a comparative analysis of turbo-driven variant application with TRB turbines and turbo-generator variant in the low power engineering. High efficiency of steam-turbine drive application with TRB turbines is proved by calculation which is made on the basis of a SE-1250-140 network pump at one of the boilers of the Republic of Belarus taken as an example. Calculation has been made for the following steam parameters: turbo-drive input – 12 kgs/cm and 250 and parameters behind turbo-drive – 1kgs/cm. Comparative analysis has been prepared on the basis of data presented by BelNIPIenergoprom in respect of regional boiler No.3 of Mogilev.